Determinant of innovation in public sector performance / Adam Syakir Mahzan - Mahzan, Adam Syakir (Faculty of Business and Management, 2019)
Whenever we heard about innovation, what comes through our mind is that it always related with private sector. This is because, private sector are known for so long to be better than the public sector in term of product or providing service. Public sector is somewhat benchmark to private sector. If the service or product produce by the public sector are already good, netizen will assume that private sector will be better. To realize a high in income nation by the year 2020 is not an easy job for the government. In order to achieve to be developed country innovation in needed. The purpose of doing this study to find out the determinant of innovation in public sector performance. This study used quantitative method which researcher distributed 230 questionnaire to four public sector organization in Muar which include Royal Malaysian Custom Department, Muar (76 employees), District Education Offices (Pejabat Pelajaran Daerah) Muar (117 employees), Majlis Perbandaran Muar (228 employees), and Pejabat Tanah Muar (75 employees). The total population for all four organizations is 496. A total of 155 set of questionnaire were returned and only 143 set were fully answered and suitable for the use of this study. The results indicated that culture, knowledge and leadership have significant relationship with innovation.